1994
DOI: 10.1046/j.1468-2982.1994.1401033.x
|View full text |Cite
|
Sign up to set email alerts
|

Head Pain in Non-Traumatic Carotid Artery Dissection: A Series of 65 Patients

Abstract: In order to assess the prevalence and characteristics of cephalic pain in internal carotid artery (ICA) dissection, and to compare clinical and angiographic features of patients with painful and non-painful dissections, we observed 65 patients with angiographically diagnosed extracranial ICA dissection from 1972 to 1990. Forty-eight patients (74%) complained of a cephalic pain which was inaugural in 38 (58.5%). It was homolateral to the dissection in 79% of cases and lasted from 1 h to 30 days, with a median o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0
21

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(118 citation statements)
references
References 10 publications
(28 reference statements)
7
90
0
21
Order By: Relevance
“…This agrees with previous studies [4][5][6][7][8]. In ICAD patients, pain was significantly more frequent in the anterior part of the head, compared to VAD, where pain occurred in the nuchal and/or occipital region.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This agrees with previous studies [4][5][6][7][8]. In ICAD patients, pain was significantly more frequent in the anterior part of the head, compared to VAD, where pain occurred in the nuchal and/or occipital region.…”
Section: Discussionsupporting
confidence: 92%
“…The exact mechanism is unknown. In 65 patients with ICAD, it was observed that previous history of migraine was more frequent in patients with painful dissection than in patients with non-painful dissection [4]. In this study, SCAD-related pain was defined as any pain that occurred before, during or after the IE.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Esse achado confi rma a alta freqüência desse sintoma, que em outros estudos variou de 55-95% 25 . A cefaléia foi seguida, na maioria dos casos, por um défi cit motor.…”
Section: Figura Paciente Do Ambulatório De Neurologia Vascular Da Epunclassified
“…1 However, when the pattern of headache or neurological symptoms are different from previous attacks, another cause may be involved, including dissection of one or more cervicocephalic arteries. 2,3 This is illustrated in the following patient. …”
mentioning
confidence: 91%